2020
DOI: 10.1371/journal.pone.0244306
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological profile of diabetic foot ulcers in Kuwait

Abstract: Introduction Diabetic foot ulcers (DFU) and infection (DFI) are a major diabetes-related problem around the world due to the high prevalence of diabetes in the population. The aim of our study was to determine the microbiological profile of infected ulcers in patients attending Dasman Diabetes Institute (DDI) clinics in Kuwait and to analyze the distribution of microbial isolates according to wound grade, sex, age and diabetes control. Methods We collected and analyzed clinical data and samples from 513 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
8
17
0
2
Order By: Relevance
“…In the EURODIALE study, male sex was found to be an independent predictor of non-healing DFU [ 38 ]. Similar findings have been reported in other populations [ 39 , 40 ]. Therefore, this could be partially explained by the hypothesis that prolonged non-healing DFU, which is more common in male patients, is likely to be the point of pathogen entry and consequently cause infections [ 28 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the EURODIALE study, male sex was found to be an independent predictor of non-healing DFU [ 38 ]. Similar findings have been reported in other populations [ 39 , 40 ]. Therefore, this could be partially explained by the hypothesis that prolonged non-healing DFU, which is more common in male patients, is likely to be the point of pathogen entry and consequently cause infections [ 28 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…In October 2021, we performed skin microbiota 16S rRNA gene high-throughput sequencing to determine bacterial infection after probiotic treatment. We used the Levine cotton swab method ( 54 ) to collect skin microbiota samples from crocodile lizards from each group. For sequencing, we constructed a 20-μl reaction system using TransGen AP221-02: TranStart Fastpfu Polymerase (TransGen Biotech, Beijing, China), including 5 × FastPfu Buffer (4 μl), 2.5 mM dNTPs (2 μl), forward primer (5 μM, 0.8 μl), reverse primer (5 μM, 0.8 μl), FastPfu Polymerase (0.4 μl), bovine serum albumin (BSA, 0.2 μl), template DNA (10 ng), and distilled water (to volume).…”
Section: Methodsmentioning
confidence: 99%
“…Gram-positive bacteria predominate in ulcers free of ischemia, while Gram-negative bacteria predominate in ulcers affected by ischemia. Pseudomonas aeruginosa was more frequent in ulcers with infection and ischemia than Staphylococcus aureus was in ulcers without ischemia [ 116 ]. The microbiological profile of DFU in Lebanon is similar to that of other nations in the Middle East and North Africa (MENA) area, with significant variances when compared with that of the Western world.…”
Section: Recent Upgrade In the Field Of Dfusmentioning
confidence: 99%